Injury Causes and Severity in Pediatric Traumatic Brain Injury Patients Admitted to the Ward or Intensive Care Unit: A Collaborative European Neurotrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) Study - Riemann, Lennart; Zweckberger, Klaus; Unterberg, Andreas; El Damaty, Ahmed; Younsi, Alexander; , Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) Investigators and Participants (Frontiers in Neurology, 2020)
Background: Traumatic brain injury (TBI) is the leading cause of death and disability in children. It includes a range of different pathologies that differ considerably from adult TBI. Analyzing and understanding injury patterns of pediatric TBI is essential to establishing new preventive efforts as well as to improve clinical management. Methods: The multi-center, prospectively collected CENTER-TBI core and registry databases were screened and patients were included when younger than 18 years at enrollment and admitted to the regular ward (admission stratum) or intensive care unit (ICU stratum) following TBI. Patient demographics, injury causes, clinical findings, brain CT imaging details, and outcome (GOSE at six months follow-up) were retrieved and analyzed. Injury characteristics were compared between patients admitted to the regular ward and ICU and multivariate analysis of factors predicting an unfavorable outcome (GOSE 1-4) was performed. Results from the core study were compared to the registry dataset which includes larger patient numbers but no follow-up data. Results: 227 patients in the core dataset and 687 patients in the registry dataset were included in this study. In the core dataset, road-traffic incidents were the most common cause of injury overall and in the ICU stratum, while incidental falls were most common in the admission stratum. Brain injury was considered serious to severe in the majority of patients and concurrent injuries in other body parts were very common. Intracranial abnormalities were detected in 60% of initial brain CTs. Intra- and extracranial surgical interventions were performed in one-fifth of patients. The overall mortality rate was 3% and the rate of unfavorable outcome 10%, with those numbers being considerably higher among ICU patients. GCS and the occurrence of secondary insults could be identified as independent predictors for an unfavorable outcome. Injury characteristics from the core study could be confirmed in the registry dataset. Conclusion: Our study displays the most common injury causes and characteristics of pediatric TBI patients that are treated in the regular ward or ICU in Europe. Road-traffic incidents were especially common in ICU patients, indicating that preventive efforts could be effective in decreasing the incidence of severe TBI in children.